2023
DOI: 10.1002/jbt.23537
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PRMT1 suppresses the malignant biological behavior of osteosarcoma cells and increases cisplatin sensitivity via c‐Myc‐mediated BCAT1 downregulation

Zhifu Li,
Dongdong Meng,
Yongyi Liu
et al.

Abstract: Increasing evidence indicated that protein arginine methyltransferase‐1 (PRMT1) is an oncogene in multiple malignant tumors, including osteosarcoma (OS). The aim of this study was to investigate the underlying mechanism of PRMT1 in OS. The effects of PRMT1 or BCAT1, branched‐chain amino acid transaminase 1 (BCAT1) on OS cell proliferation, invasion, autophagy, and apoptosis in vitro were examined. Moreover, molecular control of PRMT1 on c‐Myc or transactivation of BCAT1 on c‐Myc was assessed by chromatin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Li et al’s study provides additional evidence of PRMT1’s role in promoting osteosarcoma at the translational level. It was found that PRMT1-mediated H4R3me2a could enhance c-Myc expression, activating the mTOR signaling pathway and promoting osteosarcoma progression [ 95 ]. Methylation of STAT3 at arginine 688 by PRMT1 promoted its transcriptional activation, contributing to osteosarcoma malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al’s study provides additional evidence of PRMT1’s role in promoting osteosarcoma at the translational level. It was found that PRMT1-mediated H4R3me2a could enhance c-Myc expression, activating the mTOR signaling pathway and promoting osteosarcoma progression [ 95 ]. Methylation of STAT3 at arginine 688 by PRMT1 promoted its transcriptional activation, contributing to osteosarcoma malignancy.…”
Section: Introductionmentioning
confidence: 99%